2021
DOI: 10.1155/2021/5592191
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Privacy-Utility of Differential Privacy Mechanism: A Collaborative Perspective

Abstract: Differential privacy mechanism can maintain privacy-utility monotonicity. Thus, differential privacy mechanism does not obtain privacy-utility balance for numerical data. To this end, we provide privacy-utility balance of differential privacy mechanism with the collaborative perspective in this paper. First, we constructed the collaborative model achieving privacy-utility balance of differential privacy mechanism. Second, we presented the collaborative algorithm of differential privacy mechanism under our coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Their study emphasizes the role of privacy-preserving monotonicity in evaluating these trade-offs and explores methods for achieving optimal balances under various models. Liu et al proposed a collaborative model and algorithm for achieving a privacy-utility balance in differential privacy mechanisms, specifically for numerical data query processing [17]. Utilizing the T-Drive taxi trajectory dataset, their experiments showed that the collaborative algorithm can maintain a privacy-utility balance and achieve the required privacy-preserving and approximate data utility.…”
Section: Differential Privacymentioning
confidence: 99%
“…Their study emphasizes the role of privacy-preserving monotonicity in evaluating these trade-offs and explores methods for achieving optimal balances under various models. Liu et al proposed a collaborative model and algorithm for achieving a privacy-utility balance in differential privacy mechanisms, specifically for numerical data query processing [17]. Utilizing the T-Drive taxi trajectory dataset, their experiments showed that the collaborative algorithm can maintain a privacy-utility balance and achieve the required privacy-preserving and approximate data utility.…”
Section: Differential Privacymentioning
confidence: 99%
“…Differential privacy offers a strong privacy guarantee, even in the presence of powerful adversaries. However, achieving a balance between privacy and data utility remains a challenge, as excessive noise can affect data accuracy and analytical results [15]. Homomorphic Encryption: Homomorphic encryption enables computation on encrypted data without the need for decryption, preserving data privacy.…”
Section: Emerging Privacy Techniquesmentioning
confidence: 99%
“…To promote responsible data-driven practices while safeguarding privacy rights, organizations can tailor their privacy strategies to suit specific data contexts [15]. For scenarios requiring strict privacy preservation, approaches like differential privacy or homomorphic encryption may be more suitable, while less sensitive data sets could benefit from anonymization techniques with reduced computational overhead.…”
Section: Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation